Cooperation under fear, greed and prison: the role of redistributive inequality in the evolution of cooperation (2012)
This work offers an analysis of cooperation dilemmas making emphasis in the role of the unequal outcomes. Increases in the benefit from leaving mutual cooperation are associated to the greed dimension, while increases in the cost from leaving mutual defection are associated to fear dimension. The manipulation of these dimensions allows defining two cooperation dilemmas derived from the standard Prisoner's Dilemma. Using two different frameworks, classical game theory and evolutionary game theory, is shown that the magnitude and the direction of these inequalities have an effect over the decision of cooperation.